1999
DOI: 10.1002/(sici)1097-0142(19990815)86:4<566::aid-cncr4>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor expression in preoperative biopsy specimens correlates with disease recurrence in patients with early gastric carcinoma

Abstract: BACKGROUND Recently many studies have demonstrated that the degree of tumor angiogenesis is related to the aggressiveness of the tumor and clinical outcome. Vascular endothelial growth factor (VEGF) is a well characterized inducer of angiogenesis. In this study, the authors investigated the prognostic significance of VEGF expression in patients with early gastric carcinoma together with p53 gene abnormality and tumor cell proliferation. METHODS One hundred ninety‐five endoscopically biopsied specimens obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
5

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 19 publications
(29 reference statements)
0
65
0
5
Order By: Relevance
“…2, 4) Jones et al [82] and Suzuki et al [83] stated that enhanced vascular endothelial growth factor (VEGF) gene expression was identified to contribute to the healing of peptic ulcer, whereas Takahashi et al [84] and Maeda et al [85] reported that gastric cancer frequently displayed high levels of VEGF expression associated with intramucosal microvessel density, and Feng et al [86] indicated that high levels of VEGF expression have also been observed in gastric premalignant lesions such as chronic atrophic gastritis and intestinal metaplasia. Moreover, Tahara et al [87] indicated that the VEGF 1612A polymorphism was associated with an increased risk of gastric cancer.…”
Section: Endogenous Factorsmentioning
confidence: 99%
“…2, 4) Jones et al [82] and Suzuki et al [83] stated that enhanced vascular endothelial growth factor (VEGF) gene expression was identified to contribute to the healing of peptic ulcer, whereas Takahashi et al [84] and Maeda et al [85] reported that gastric cancer frequently displayed high levels of VEGF expression associated with intramucosal microvessel density, and Feng et al [86] indicated that high levels of VEGF expression have also been observed in gastric premalignant lesions such as chronic atrophic gastritis and intestinal metaplasia. Moreover, Tahara et al [87] indicated that the VEGF 1612A polymorphism was associated with an increased risk of gastric cancer.…”
Section: Endogenous Factorsmentioning
confidence: 99%
“…17 Expression of VEGF, a multifunctional cytokine, is crucial in angiogenesis during the development of cancer and correlates with disease recurrence in patients with early gastric carcinoma. 18 p38 MAP kinase activation by VEGF mediates actin reorganization and cell migration in human endothelial cells. 19 By modulating cell migration, p38 may thus be an important regulator of angiogenesis.…”
Section: Genes Related To Extracellular Matrixmentioning
confidence: 99%
“…However, these factors cannot be used for predicting lymph node metastasis at the preoperative stage. Previous groups have therefore sought to identify biomarkers for predicting lymph node metastasis 11,25,27 . Since lymph node metastases are present in only 3±5 per cent of mucosal tumours, but in 10±25 per cent of submucosal tumours 1 , it is also important to assess invasion depth before operation in early gastric cancer.…”
Section: Introductionmentioning
confidence: 99%